Rapid and easy identification of genes associated with nanoparticles from plant protein structure database - Asra Parveen; Vijaykumar-B. Malashetty; Prakasham-Reddy Shetty; Vinod Patil; Raghunandan Deshpande (Elsevier, 2022)
The study provides simple protocol for identifying unknown genes (DNA and RNA) and proteins present in the plants. The exact mechanism of nanoparticle synthesis from plant extracts is still unclear. Although functionalization of nanoparticle has been achieved by binding biomolecules and stabilizing through exchange of ligands and electrostatic interactions. This study will help in case of difficulty in extraction of proteins and DNA from nanoparticles due to less sample collection or degradation of active biomolecules. Plant extracts holds various biomolecules and can be used to presume the basic formulae of plant proteins by using software. The presence of DNA traces on silver nanoparticles confirmed and DNA sequence was extracted from NCBI gene bank. Homology modeling is an alternative method to predict 3D structure of proteins in the absence of experimental results. DNA gel electrophoresis and quantification of biomolecules and 3D protein structures have built from known sequences of conforming family members of protein using SWISS-MODEL. A major advantage of automated homology modeling is creating protein models that are easy to design the structure. Protein sequencing is continuously evolving nowadays. Experts are improving SWISS-MODEL to enhance the efficient transition. The study will help in easy and rapid identification of genes and proteins present on the surface of biological nanoparticles. Structural analysis of protein (proteomics) helps to identify novel functions that could facilitate designing of efficient biosensors.